The Infinite Self: A Philosophy on the Origin and Nature of Consciousness - Breslauer, Sam (Journal of NeuroPhilosophy, 2023)
The origin and nature of consciousness remains a deeply perplexing mystery for material scientists. Many material approaches towards the study of consciousness have been employed but have struggled to scratch beyond the surface of this strange yet intimately familiar phenomenon of the universe. This paper aims to provide a refreshingly new perspective that explains various theological, philosophical and physical interconnections that help solve the puzzle of consciousness. At the heart of this model is the notion that the material universe relies on the initial existence of an eternal Creator, whose central characteristic is Self-consciousness. It is the Self-love that emerges from the infinite consciousness of the Creator that provides the cause for ‘creation itself’ and explains how the differentiated material universe emerges from a unified immaterial origin. However, although creation relies on the primordial presence of the Creator, the Creator in turn relies on the existence of the infinite void of Nothingness.